2014
DOI: 10.1007/s11743-013-1558-x
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and Surface Properties of Anionic Gemini Surfactants having N‐acylamide and Carboxylate Groups

Abstract: A straightforward synthetic strategy to an anionic gemini surfactant having both N‐acylamide and carboxylate groups in a molecule has been demonstrated. The surface properties of the anionic gemini surfactant, such as CMC (critical micelle concentration), C20 (the concentration required to reduce the surface tension of the solvent by 20 mN/m), γCMC (the surface tension at the CMC), ∏CMC (the surface pressure at the CMC), Γmax (the maximum surface excess concentration at the air/aqueous solution interface), Ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In contrast, the CMC values of noncovalently bonded pseudogemini surfactants are higher than those reported for “true” covalently bonded carboxylate gemini surfactants with a small spacer (ethylene), such as (CH 2 ) 2 [N(COC n H 2n+1 )‐CH(COOH)CH 2 COOH]·2NaOH ( n + 1 = 12, 14, and 16, CMC = 0.0085, 0.00079, and 0.0039 mM) (Tsubone et al, ) and 1,2‐bis(N‐β‐carboxypropanoyl‐N‐alkylamino)ethane (2C n enAm, n = 12 and 14, CMC = 0.01 and 0.0026 mM) (Yoshimura and Esumi, ). The CMC values are comparable, however, to those reported for “true” carboxylate gemini surfactants with a large spacer (more than six mthylene carbons), such as N,N′‐hexamethylene‐bis(dodecylsuccinamic acid) (CMC = 0.10 mM) (Zhou et al, ). On the other hand, the CMC values of noncovalently bonded pseudogemini surfactants are noticeably lower than those of their monomers (Rosen, ), embodying the advantages of gemini surfactants.…”
Section: Resultssupporting
confidence: 55%
“…In contrast, the CMC values of noncovalently bonded pseudogemini surfactants are higher than those reported for “true” covalently bonded carboxylate gemini surfactants with a small spacer (ethylene), such as (CH 2 ) 2 [N(COC n H 2n+1 )‐CH(COOH)CH 2 COOH]·2NaOH ( n + 1 = 12, 14, and 16, CMC = 0.0085, 0.00079, and 0.0039 mM) (Tsubone et al, ) and 1,2‐bis(N‐β‐carboxypropanoyl‐N‐alkylamino)ethane (2C n enAm, n = 12 and 14, CMC = 0.01 and 0.0026 mM) (Yoshimura and Esumi, ). The CMC values are comparable, however, to those reported for “true” carboxylate gemini surfactants with a large spacer (more than six mthylene carbons), such as N,N′‐hexamethylene‐bis(dodecylsuccinamic acid) (CMC = 0.10 mM) (Zhou et al, ). On the other hand, the CMC values of noncovalently bonded pseudogemini surfactants are noticeably lower than those of their monomers (Rosen, ), embodying the advantages of gemini surfactants.…”
Section: Resultssupporting
confidence: 55%
“…When the concentration was less than the CMC, surfactant conductivity increased rapidly with increasing concentration. When the concentration was greater than the CMC, the conductivity increased with increasing concentration, but at a slower rate (Zhou et al, ). The CMC was obtained from the turning point of the lines from the plots of specific conductance versus surfactant molar concentration.…”
Section: Methodsmentioning
confidence: 99%
“…In 2001, Dix reported a new anionic Gemini surfactant using the unsaturated succinic anhydride and diamine as starting materials for the first time (Dix, 2001;Dix & Gilblas, 2005). The critical micelle concentration (CMC) of the anionic Gemini surfactants was around 0.1 mM in aqueous solution at 20 C. On the basis of Dix's work, Zhou et al (2014) reported another anionic Gemini surfactant with saturated succinic anhydride in 2014, which showed a similar CMC. In this paper, we designed a straightforward, mildly synthetic route toward an anionic Gemini surfactant using saturated succinic anhydride and 1,8-diamino-3,6-dioxaoctane as starting materials as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic groups are connected by a short linker at, or in close vicinity to, the headgroup (Menger and Littau, ). Due to their special structure, Gemini surfactants are superior to the corresponding monomeric surfactants in certain characteristics (Zana, ; Zhou et al, ). One of the key properties of Gemini surfactants is the remarkably low critical micelle concentration ( cmc ) in aqueous media, which enables us to reduce the total consumption of surfactants in waterborne chemical products.…”
Section: Introductionmentioning
confidence: 99%